Analisis konsentrasi dan distribusi spasial logam berat dalam air tanah di sub DAS Galeh-torong, Jawa Tengah, Indonesia - Wacano, Dhandhun; Febrianti, Nedhia; Ardhayanti , Lutfia Isna (Jurnal Kesehatan dan Pengelolaan Lingkungan, 2025)
Groundwater is the most desired natural resource to fulfill daily needs of humans in the world. The lake of Rawa Pening has undergone a decline in water quality due to both external and internal activities that pose a risk of pollution. Environmental pollution in the surrounding lake of Rawa Pening is not only indicated by the proliferation and expansion of water hyacinth plants but also from heavy metals. This study examined the concentration and spatial distribution of Cd, Cu, Pb, and Fe in the groundwater of Sub DAS Galeh-Torong, the western part of Rawa Pening, to better understand the threats in the Rawa Pening Lake circumstance. A total of 18 groundwater samples were collected and analyzed using atomic absorption spectrophotometry (AAS). Inverse distance weighted (IDW) was applied to reveal the spatial distribution combined with the standard threshold classification pattern. The result showed that the concentration of Cd, Pb, and Fe was exceeding the Indonesian standard for drinking water, while Cu did not. Further, the spatial distribution pattern revealed that the eastern part of the study area was consistently in high concentration for all of the metals. The location is flat in morphology and is associated with intensive human activities such as settlement areas, agriculture areas, and tourism areas. The impact of heavy metal exposure through drinking water should become a highlighted issue in the study area since the toxicity of heavy metals can have a lethal impact. The information of concentration and spatial distribution is crucial to the better management of water resource security and sustainability.